Electromembrane Processes : Theory and Applications (De Gruyter STEM, 2021)
The book is a comprehensive view of all electromembrane processes, including electromembrane processes for energy conversion - a currently very significant problem. The necessary theory and basic information needed for understanding the technology are explained in Part I. Materials used for ion-selective membranes and seoaration processes are described in Part II, and the applications for synthesis and energy conversion in Part III.